Knee Preservation Techniques for Severe Synovial Osteochondromatosis in End-Stage Osteoarthritic Knee Using High Tibia Osteotomies, Cartilage Restoration Procedure, and Biologics; A Case Report in Bilateral Knees - Andre Yanuar; Dwikora Novembri Utomo (The Hip and Knee Journal, 2020)
Synovial osteochondromatosis can occur idiopathic or secondary to osteoarthritis. While joint replacement surgery has shown promising results for end-stage osteoarthritis, it isn’t always the answer for certain individual. In young athletic individual, the treatment should be patient specific, with consideration for return to sports activities. We present a 48-year-old ex-national professional football player with significant osteoarthritis and severe synovial osteochondromatosis. After discussion with the patient, we decide that knee preservation is suitable for him. Surgical treatments that are considered the best option are High Tibial Ostetomies, extraction of the loose bodies, partial synovectomy, and microfracture. Those procedures were performed in 8 months interval for each knee. The patient received intra-articular injection of cultured Mesenchymal Stem Cells (MSCs) with hyaluronic acid for 4 weeks after surgery. In a 34-month follow-up for right knee and 26-month follow-up for left knee, the patient regained significantly higher Knee injury and Osteoarthritis Outcome Score (KOOS) compare to before surgery (94 vs. 47). Radiologic examination also reveals the improvement of both knees joint space.